Shared decision making: a need for honesty? - Ives, J; Papanikitas, A; Myres, P; Gregory, S (Royal College of General Practitioners, 2018)
In this analysis we challenge the conceptual honesty of ‘shared decision-making’, arguing that whilst it is held up as an ideal decision-making standard, it is used too often to describe (and justify) decision-making practices that are not shared at all. This is problematic because if the legitimacy of a decision relies on it being ‘shared’, but it is not in fact shared, the decision loses legitimacy, or is falsely legitimised by the appearance of being shared. We argue that the realities of clinical practice mean that genuinely shared decision-making is not completely impossible but difficult to achieve in a sincere and just manner. We articulate an intentionally controversial stance, with the aim of generating thought and debate.